Membrane bioreactor and integrated membrane bioreactor systems for micropollutant removal from wastewater: A review. (December 2018) - Goswami, Lalit; Vinoth Kumar, R.; Borah, Siddhartha Narayan; Arul Manikandan, N.; Pakshirajan, Kannan; Pugazhenthi, G.
Highlights: Potential application of MBR and integrated MBR system for micropollutant removal. Fate and removal mechanism of micropollutants in MBR. Factors affecting the MBR system efficiency. Operating cost assessment for the future circular economy. Abstract: Over the last few decades, the presence of micropollutants in the wastewater stream is imposing a serious concern worldwide. Membrane bioreactor (MBR) technology has been widely employed for the treatment of wastewater contaminated with micropollutants. Hence, the aim of this paper is to provide a consolidate review on the present state of research and advancement in MBR technology along with its augmentation with other wastewater treatment technologies for micropollutant removal, sustainability, and operating cost assessment for its feasibility. The potential application of MBR and hybrid-MBR systems in micropollutant removal along with the fate, removal mechanism, various factors affecting the MBR system efficiency and the operational cost involved were also been discussed in detail. Further, based on the available technologies on MBR, the authors discussed the future research perspective for micropollutant removal from the effluent stream with an objective of the circular economy.